Blue‐stain fungi isolated from freshly felled Scots pine logs in Poland, including Leptographium sosnaicola sp. nov. Issue 2 (22nd January 2021) - Jankowiak, Robert; Szewczyk, Grzegorz; Bilański, Piotr; Jazłowiecka, Dominika; Harabin, Beata; Linnakoski, Riikka
Abstract: Wounds on felled tree stems provide entrance to inner wood for many fungi, including blue‐staining fungi, which cause permanent discoloration of wood. The aim of work presented here was to explore the diversity of blue‐stain fungi and assess the influence of the felling method and storage time/sampling period on their abundance and species diversity. Scots pines ( Pinus sylvestris ) grown in Poland were cut in April and July 2016, and fungal isolations from 20 stained logs that were obtained by mechanized harvesting and chainsaw harvesting, were carried out 3, 6, 9 and 12 weeks after felling. In total, eight fungal taxa were identified, including seven known and one novel species. Among the blue‐staining fungi detected, seven taxa belonged to Ophiostomatales, and one was identified as Sphaeropsis sapinea . The most frequently isolated fungi were S. sapinea, Ophiostoma minus and Ophiostoma ips . Additionally, Graphilbum acuminatum, Leptographium sosnaicola sp. nov., O. floccosum, O. piliferum and Sporothrix eucastaneae were found. More fungal isolates were obtained from summer‐harvested logs than spring‐harvested logs and from chainsaw‐harvested logs than mechanically harvested logs.